Rheological behaviors of concentrated suspensions in pressure-driven tube flow - Wang, Zhiying (2008)
The flows of concentrated suspensions occur in many practical applications. Thus the characterization and understanding of their rheological behaviors are important. Ethylene vinyl acetate (EVA) 460 and glass microspheres were used as the model suspension system. Rheological measurements were conducted on the binder system of pure polymer EVA460 and the concentrated suspension with glass microspheres dispersed in EVA460 polymer melt. In the characterization of the rheological behavior of pure EVA and concentrated suspension in capillary flow, entrance and exit losses and slip velocity should be obtained. Entrance and exit losses were measured using an orifice die and were calculated by Bagley correction. Due to the difficulty in ensuring the extruded suspension to be clear from the die wall in the expansion region of the orifice die, the entrance and exit losses measured by the orifice die were higher than those by Bagley correction. It was also observed that Bagley plot exhibited good linearity for EVA but not for concentrated suspension. In addition, for concentrated suspension, the nonlinearity increased with increasing particle concentration.